BIOMETRIC ASPECTS IN TREATMENT OF COMBINED TRAUMA - E. K. Gumanenko; Yu. A. Scherbuk; M. G. Silyuk; K. P. Golovko; O. D. Maday; N. A. Udaltsova; E. А. Gorshkov; А. O. Bumay; A. G. Afinogenova; G. E. Afinogenov; D. Yu. Maday (Вестник хирургии имени И.И. Грекова)
The objective is to determine the optimal tactics in treatment of combined trauma using the objective assessment of the severity of injuries and the overall condition of the casualties.Material and methods. The article presents the materials on biometric analysis of treatment of casualties with combined trauma in the program of multi-staged surgical treatment.Results. In the process of multi-staged surgical treatment, we can determine the prognosis, the nature of the traumatic disease with the help of a biometric comprehensive study that will optimize comprehensive treatment program and rehabilitation of casualties in the trauma center of the 1st level.Conclusion. The conditions for the application of the full spectrum of surgical interventions in the maxillofacial region in the acute period of traumatic disease are created in favorable prognosis. The choice of treatment in favorable or unfavorable prognosis is a multistaged surgical tactics of treatment – Damage control surgery.